2021
DOI: 10.3390/cells10123411
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Physiological Investigation of a New Arthrospira/Limnospira Strain O9.13F Isolated from an Alkaline, Winter Freezing, Siberian Lake

Abstract: Cyanobacteria from the genus Arthrospira/Limnospira are considered haloalkalotolerant organisms with optimal growth temperatures around 35 °C. They are most abundant in soda lakes in tropical and subtropical regions. Here, we report the comprehensive genome-based characterisation and physiological investigation of the new strain O9.13F that was isolated in a temperate climate zone from the winter freezing Solenoye Lake in Western Siberia. Based on genomic analyses, the Siberian strain belongs to the Arthrospir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
(141 reference statements)
0
5
0
1
Order By: Relevance
“…1999), Arthrospira Stizenberger ex Gomont (Miklaszewska et al . 2012; Misztak et al . 2021), Synechococcus , Planktothrix , Pseudanabaena Lauterborn, Nodularia, Nostoc , Calothrix (Miklaszewska et al .…”
Section: Resultsunclassified
“…1999), Arthrospira Stizenberger ex Gomont (Miklaszewska et al . 2012; Misztak et al . 2021), Synechococcus , Planktothrix , Pseudanabaena Lauterborn, Nodularia, Nostoc , Calothrix (Miklaszewska et al .…”
Section: Resultsunclassified
“…and it is, therefore, premature to conclude how these two species differ. Nonetheless, a recent comparative genomic analysis (Misztak et al, 2021) proposed that the two species are, in fact, in two different Arthrospira groups, thus questioning whether tool transferability could be achieved in these two hosts.…”
Section: Limited Genetic Tools Have Been Developed and Applied In Mar...mentioning
confidence: 99%
“…Cyanobacteria from the genus Arthrospira/Limnospira are considered haloalkalo-tolerant organisms with optimal growth temperatures of approximately 35 °C. They are most abundant in soda lakes in tropical and subtropical regions [ 1 ]. Indeed, the paper by Misztak et al is devoted to the comprehensive genome-based characterization and physiological investigation of the new strain O9.13F, which was isolated from the winter freezing Solenoye Lake in Western Siberia [ 1 ].…”
mentioning
confidence: 99%
“…They are most abundant in soda lakes in tropical and subtropical regions [ 1 ]. Indeed, the paper by Misztak et al is devoted to the comprehensive genome-based characterization and physiological investigation of the new strain O9.13F, which was isolated from the winter freezing Solenoye Lake in Western Siberia [ 1 ]. Comparative genomics showed that no unique genes were found for the Siberian strain related to its tolerance to low temperatures and high salinity, while the fatty acid composition was specific and unique to this strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation